Sweatshops at sea : merchant seamen in the world's first globalized industry, from 1812 to the present - Fink, Leon, 1948- (University of North Carolina, 2011)
Fink explores both how political and economic ends are reflected in maritime labor regulations and how agents of reform--including governments, trade unions, and global standard-setting authorities--grappled with the problems of applying land-based, national principles and regulations of labor discipline and management to the sea-going labor force.